(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2025)
The San Juan Bautista church in Huaytara, Peru, was built by order of Inca Pachacutec in 1497 as part of the Inca Empire’s expansion. Over the years, it has witnessed various historical events and undergone alterations, making it unique in terms of construction materials used in Latin America. However, due to a lack of conservation, it exhibits noticeable damage, particularly in the adobe walls, Inca wall, and facades. The focus of this work is a nonlinear structural analysis of the church to assess its behavior under seismic actions. It begins with a review of the current state and a historical investigation into the construction phases. Next, a 3D geometric model is generated using photogrammetric techniques, followed by a detailed description of the structural components and materials encountered during fieldwork. Mechanical characterization of the materials is conducted through laboratory tests in Lima and Barcelona. Finally, a 3D numerical model using finite element analysis is developed to evaluate the structural response to gravitational and seismic loads, employing the nonlinear static method (Pushover). This allows for the identification of the current damage causes and the most vulnerable elements of the church.